Introduction of the Community Rehabilitation Northern Queensland Service - Merehau Cindy Mervin (Asia Pacific Journal of Health Management, 2017)
Objective: To analyse trends in length of hospital stay before and after the implementation of the Community Rehabilitation Northern Queensland Service (CRNQ) in Townsville, Australia.